Effect of acidic beverages on color stability and microhardness of various esthetic restorative materials: A comparative study - Aradhana Rathod; Suneel V Vadavadagi; Tanya Verma; Pawan Kumar; Potluri Venkataratna Deepak; Saikat Deb; Azhar Iqbal (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to assess the effect of acidic beverages on color stability and microhardness of various esthetic restorative materials. Materials and Methods: A total of 60 samples were included in the present study. Group I: Microhybrid composite resin, Group II: Nanoceramic, Group III: ORMOCER (Organically Modified Ceramics). 10 mm internal diameter and 5 mm depth of cylindrical aluminum mold of were utilized to prepare the samples. All the esthetic restorative samples were submerged for 10 min in 25 ml of acidic drink (Coca-Cola) each day up to 15 days. Vickers diamond intender was used to measure the microhardness of each sample. These values were calculated with baseline, 7th, and 15th days for final microhardness values. Results: The mean surface microhardness of 63.20 ± 0.46 was shown by Group III which was slightly more than that in Group II (60.08 ± 0.34) and Group I (58.10 ± 1.76). Analysis of covariance did not show any statistically significant difference between the groups. The samples in Group I showed the highest reduction in surface microhardness value after immersion into acidic drink, followed by Group II and Group III on 7th day and 15th day. A statistically significant difference (P < 0.001) was found on the 7th day. Conclusion: The present study concludes that the Organically Modified Ceramics esthetic restorative material showed the finest behavior after being dipped in the acidic drink followed next by Nanoceramic and Microhybrid composite resin.